Accumulation of Free Amino Acids in Different Organs of Green and Red Mustard Cultivars - Bok Kim1, Yeon; Romij Uddin1, Md; Lee2, Min-Ki; Kim2, Sun-Ju; Hoon Kim3, Haeng; Chung4, Eunsook; Lee4, Jai-Heon; Un Park1, Sang (Asian Journal of Chemistry, 2014)
Mustard (Brassica juncea) is an important oil crop in the Brassicaceae family, containing a variety of amino acids. The present study investigated the variation in amino acids among the different tissues of green and red mustard cultivars. The levels of these amino acids varied significantly among tissues and between cultivars. A markedly higher quantity of all of the amino acids was observed in young leaf tissue, compared to other parts of the plant, in both cultivars. Among the free amino acids, concentrations of leucine, lysine, arginine, alanine, valine and phenylalanine were much higher than those of any other amino acids. In green mustard cultivars, young leaf tissue contained 3.6, 1.3, 17.5 and 63.2 times greater total amino acid content than stem, flower, seed and root, respectively. Young leaf tissue of red mustard cultivars contained 11.56, 1.1, 9.6 and 35.1 times greater total amino acid content than stem, flower, seed and root, respectively. Considering the total amino acid contents from all organs, the green cultivar contained 1.3 times more amino acids than the red cultivar. Present results demonstrate that mustard cultivars contain varying amounts of free amino acids among plant tissues and suggest that these cultivars have excellent potential to serve as a source of amino acids in vegetable plants.